Improving the Quality of Operator Tri's 2G 4G Network Based on Walktest Data at Minangkabau International Airport - Sitti Amalia; Yona Pramunita Rusali; Andi Sofyan (CV. Rayyan Dwi Bharata, 2024)
This research investigates improving the quality of 2G and 4G networks for Tri operators at Minangkabau International Airport through walktest data analysis. By leveraging tools such as Tems Investigation and Actix Analyzer, parameters such as RSRP, SINR, RxLevSub, and RxQual are evaluated to optimize network performance. This research aims to meet KPI standards and improve user experience by ensuring smooth connectivity. These findings provide valuable insights into network optimization strategies.